EVALUATION BUSINESS STRATEGY NEIRA COFFE SHOP USING BUSINESS MODEL CANVAS APPROACH - Muchammad Ramelan (Universitas Mercu Buana, 2021)
The high competition in the coffee shop business and promising opportunities make Neira coffee shops able to adapt and develop their business. This study aims to evaluate the business strategy of the Neira coffee shop with a canvas model business approach as well as to design a new business model through five porter analysis and SWOT analysis including identification of internal and external factors. This research is a descriptive qualitative research with indept interview method. The results of this research show that the development of a business model in seven blocks on the canvas business model, namely the development of the customer segment is a type of professional worker or entrepreneur. In Customer Relationship, the development obtained is push notification email/ WhatsApp; Revenue Streams development is a consignment fee; Key Resources development is a customer database; Key Activity development is a continuous online promotion; Key Partnership development is namely partnering with bakery shops; and development on the Cost Structure is the cost of developing innovation